I = sqrt(-1)
i^2 = -1
(-i)^2 = (-i)(-i) = i^2 = -1
(-i)^3 = (-i)(-i)(-i) = (-i)(i^2) = i
use these facts to find which equation is correct if x = -i
i bet on 2,3 or 4
Two figures are congruent if and only if there exists one or more rigid motions which will map one figure onto the other.
1. Triangles ABC and MNP are not congruent.
2. Triangles ABC and EFG are not congruent
3. Triangles ABC and STU are congruent.
4. Triangles EFG and MNP are congruent.
5. Triangles EFG and STU are not congruent.
6. Triangles STU and MNP are not congruent.
We can solve this using substitution.
because x-y=2.5
x=y+2.5
Now substitute x into other equation.
2(y+2.5)^2-2y=125
2y^2+10y+12.5-2y=125
2y^2+8y-112.5=0
Now comes the ugly part
y=-4+-sqrt(16+900)
y=-4+-sqrt916
y=-4+-2sqrt229
x=-1.5+-2sqrt229
Answer:
Step-by-step explanation:
106n=310
n=300/106=150/53